The "conquest" of Acadia, 1710 : imperial, colonial, and aboriginal constructions - Reid, John G., 1948- (University of Toronto Press, 2004)
The 'Conquest' of Acadia will be a significant contribution to Acadian history, native studies, native rights histories, and the socio-political history of the eighteenth century.